Responding to the Grand Challenge to End Homelessness: The National Homelessness Social Work Initiative. Issue 3 (July 2016) - Larkin, Heather; Henwood, Benjamin; Fogel, Sondra J.; Aykanian, Amanda; Briar-Lawson, Katharine H.; Donaldson, Linda Plitt; Herman, Daniel; Little, Samuel B.; Meyer-Adams, Nancy; Padgett, Deborah K.; Patchner, Michael A.; Streeter, Calvin L.
The American Academy of Social Work and Social Welfare adopted ending homelessness as one of its 12 Grand Challenges for Social Work. The National Center for Excellence in Homeless Services supports this Grand Challenge through its National Homelessness Social Work Initiative. This initiative is being carried out through a consortium of schools of social work nationally, emphasizing workforce development and policy advocacy. This major, multiyear initiative applies innovative strategies to service and policy design and social work education. This article describes the overall mission of the Homelessness Initiative and key activities used to strengthen social work curriculum, expand homelessness-related field placement opportunities for students, and impact services through the policy advocacy and dissemination of best practices.